Corporate social responsibility, gender equality and organizational change: a feminist perspective - Grosser, Kate (2011)
There is a growing literature on corporate social responsibility (CSR) and gender issues, which draws upon a range of feminist theory and perspectives. However,research in this field appears to have been somewhat hampered by a lack of systematic engagement with ‘gendered organizations’ studies (GOS), and with a broad range of CSR theory, in particular that related to governance. This thesis sets out to address these gaps in the literature. It opens up new dialogue between the fields of GOS and CSR. Through a review of the GOS literature this study notes a number of organizational change strategies identified by feminist scholars. With reference to these it develops a set of research questions with which to investigate the possible contribution of CSR to organizational change with regard to gender equality. These are then employed in an exploration of CSR practice, focusing on CSR reporting and stakeholder relations. Through this analysis the thesis identifies several ways in which CSR might contribute to advancing the feminist organizational change agenda. Particular attention is paid to recent developments in political theories of CSR, which regard CSR as a governance process involving business, government and civil society. Thus, the thesis addresses organizational change and gender equality in the context of new governance, and particularly CSR, and by extending the literature both empirically and conceptually produces insights for feminist studies relating to CSR theory and practice.